Physiologic determinants of prolonged mechanical ventilation in patients after major surgery - KARAKURT, SAİT (W B SAUNDERS CO-ELSEVIER INC, 2012)
Purpose: The aim of the study was to evaluate the physiologic determinants of ventilator dependency in patients who underwent major surgery. Materials and Methods: In this observational study, 43 stable tracheostomized patients undergoing prolonged ventilation (>14 days) were evaluated. Diaphragmatic muscle function was assessed invasively by the tension-time index of the diaphragm (TTdi), an indicator of diaphragm endurance time. The TTdi was calculated as transdiaphragmatic pressure/maximum transdiaphragmatic pressure x inspiratory time/total respiratory time and was recorded either when weaning from mechanical ventilation had finally been successful (n = 28 patients) or at the end of the fifth week in those patients in whom weaning failed (FW) (n = 15). Furthermore, the characteristics of survivors (n = 33) were compared with those of nonsurvivors (n = 10). Results: Successfully weaned patients had a lower breathing frequency/tidal volume or rapid shallow breathing index compared with FW patients (93.9 +/- 45.5 vs 142.4 +/- 60.3, respectively; P < .005). The TTdi was significantly higher in FW than in successfully weaned patients (0.107 +/- 0.050 vs 0.148 +/- 0.059; P < .023) and in nonsurvivors than in survivors (0.106 +/- 0.046 vs 0.174 +/- 0.058, P < .0001, respectively). A transdiaphragmatic pressure/maximum transdiaphragmatic pressure ratio of more than 40% was an independent predictor of mortality, whereas an increased frequency/tidal volume ratio and TTdi were independent predictors of weaning failure. Conclusions: Difficult-to-wean patients after major surgery have overall a limited diaphragm endurance time, in particular, FW breathe very close to the fatigue threshold, and they adopt a rapid shallow breathing respiratory pattern to avoid crossing this threshold. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: Mechanical ventilation; Weaning; Surgery; Respiratory mechanics; CRITICALLY-ILL PATIENTS; DIAPHRAGMATIC FUNCTION; PRESSURE; FAILURE; SUCCESS